2011
DOI: 10.1007/s00423-011-0761-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of gene-modified keratinocytes and fibroblasts to enhance regeneration in a full skin defect

Abstract: The results suggest that our two-layer, gene-modified artificial skin improved both vascularization and epidermalization for skin regeneration. This technique could bring about a new approach in the treatment of burns and chronic wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…A few studies have been performed using VEGF to enhance wound healing. Altering fibroblast VEGF expression has shown potential increases in wound healing and angiogenesis[102,103]. Yet increasing VEGF has also been shown to increase fibrosis and scar formation in skin[104,105].…”
Section: Components Of a Skin Substitutementioning
confidence: 99%
“…A few studies have been performed using VEGF to enhance wound healing. Altering fibroblast VEGF expression has shown potential increases in wound healing and angiogenesis[102,103]. Yet increasing VEGF has also been shown to increase fibrosis and scar formation in skin[104,105].…”
Section: Components Of a Skin Substitutementioning
confidence: 99%
“…VEGF is a well-established therapeutic protein for enhancing angiogenesis both in vitro and in vivo . Our and many other groups have previously shown that secreted VEGF can enhance cell proliferation, wound healing and angiogenesis in different pre-clinical models [24, 49, 50]. In present study, our main focus was not on the effect of VEGF on proliferation of cells on scaffolds but rather if scaffolds can be used as carriers for cells which are genetically engineered to secrete VEGF or other therapeutic proteins.…”
Section: Discussionmentioning
confidence: 96%
“…These engineered skin components allowed for optimal conditions (otherwise both keratinocytes and fibroblasts lack support from other supporting cells) that led to a well-organized epidermis, structured dermis, and effective vascularization [18]. Of note, constant expression of the transgenes was apparently unnecessary, as transient levels mediated by the adenoviral vector were sufficient to enhance skin regeneration [18]. Finally, corneal allografts-as a direct consequence of their prolonged viability (up to four weeks without significant loss of function) prior to transplant-have been subjected to ex vivo gene therapy to prevent allograft rejection [19].…”
Section: Gene Modified Cellsmentioning
confidence: 98%
“…In one such study, both epidermal keratinocytes and dermal fibroblasts genetically modified to express important factors necessary for optimal skin repair: platelet-derived growth factor BB (PDGF-BB), vascular endothelial growth factor (VEGF), and basic fibroblast growth factor (bFGF). These engineered skin components allowed for optimal conditions (otherwise both keratinocytes and fibroblasts lack support from other supporting cells) that led to a well-organized epidermis, structured dermis, and effective vascularization [18]. Of note, constant expression of the transgenes was apparently unnecessary, as transient levels mediated by the adenoviral vector were sufficient to enhance skin regeneration [18].…”
Section: Gene Modified Cellsmentioning
confidence: 99%